2020
DOI: 10.1001/jamanetworkopen.2020.3277
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Insurance With Survival Among Patients With Small Cell Lung Cancer

Abstract: IMPORTANCE Small cell lung cancer (SCLC) is an aggressive neoplasm requiring rapid access to subspecialized multidisciplinary care. For this reason, insurance coverage such as Medicaid may be associated with oncologic outcomes in this disproportionately economically vulnerable population. With Medicaid expansion under the Affordable Care Act, it is important to understand outcomes associated with Medicaid coverage among patients with SCLC. OBJECTIVE To determine the association of Medicaid coverage with surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
3
16
0
Order By: Relevance
“…Consistent with our findings, private and Medicare insurance were found to be associated with survival benefit in patients with SCLC, regardless of stage, although Medicaid was not associated with improved survival. 34 Similarly, MacLean et al 35 obtained data from 2006 to 2012 to compare the application of neoadjuvant and adjuvant chemotherapy in stage II and III NSCLC. Private insurance was shown to provide more survival advantage compared with public insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, private and Medicare insurance were found to be associated with survival benefit in patients with SCLC, regardless of stage, although Medicaid was not associated with improved survival. 34 Similarly, MacLean et al 35 obtained data from 2006 to 2012 to compare the application of neoadjuvant and adjuvant chemotherapy in stage II and III NSCLC. Private insurance was shown to provide more survival advantage compared with public insurance.…”
Section: Discussionmentioning
confidence: 99%
“…There have been contradictory data on the impact of insurance and survival in patients with SCLC. One study found that Medicaid was not associated with a survival benefit compared with being uninsured for patients with SCLC, 39 whereas another revealed worse survival for Medicaid patients. 17 , 40 In our cohort, private insurance was associated with the highest OS (9.2 mo), and patients with Medicaid had the second-highest survival (8.3 mo).…”
Section: Discussionmentioning
confidence: 99%
“…One study of patients with lung cancer found that Medicaid was not associated with improved overall survival compared with noninsurance, suggesting the need for further intervention at the policy level. 19 A recent study found that in patients with lung, colorectal, and breast cancer had improved survival with Medicaid expansion. 20 Cervical cancer is a highly screenable cancer in which Medicaid expansion may have a significant impact.…”
Section: Introductionmentioning
confidence: 99%